Art as Civic Inspiration. (January 2020) - Perkins, David
Today as in the past, artists often produce works of art to foster civic agendas of one sort or another, sometimes affirming and sometimes critiquing contemporary attitudes. To what degree is engaging with civically inflected art likely to have the desired impact? We develop an analogy between the work of Ellen Winner and colleagues questioning the impact of studying art on performance in other academic areas. We suggest that, in many cases of civically inflected art, transfer of the desired message is implausible, recognizing difficulties of changing people's minds in general, of how art specifically might do so, and how superficially art is often engaged. We urge that civically impactful encounters with art, which certainly occur, require not just a landing pad character—the impact deriving from imbibing the work—but rather a launching pad character—the work functioning as a starting point for discussion, reflection, and exploration.